Introduction to podoconiosis - Davey, Gail (Henry Stewart Talks, 2019)
An overview of podoconiosis, Mapping and Epidemiology of podoconiosis, The economic, social, and mental health burden of podoconiosis, The genetic and environmental sides of podoconiosis, Clinical features and stages of podoconiosis, Prevention of podoconiosis, The GoLBeT trial, Research into advocacy